PEMBERDAYAAN EKONOMI MELALUI KELOMPOK TANI MAJU MEKAR DALAM MENYEJAHTERAKAN ANGGOTANYA - Ajang Suryana; Syamsuddin RS; Deden Sumpena (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2024)
This research aims to determine the process of economic empowerment, marketing strategies for Boehoen coffee products, and the results of economic empowerment of the Maju Mekar farmer group in Nagarawangi Village. This research is qualitative research using descriptive methods. The results of empowerment through the Maju Mekar farmer group are in three categories, namely the empowerment process, marketing strategy and empowerment results. In the process there are three stages, namely awareness, knowledge transformation stage and intellectual ability improvement stage. The marketing strategy used is expanding the marketing network, maximizing opportunities, playing in terms of quality, using online media. The following are the results of the economic empowerment that has been carried out, namely having freedom of mobility, the ability to buy small commodities, the ability to buy large commodities, always participating in decisions regarding household matters, having freedom of family domination, understanding government regulations, being involved in voicing aspirations, having legal guarantees. economy and sharing for families.